A design of broadband dual circularly polarized antenna. Issue 7 (8th April 2021) - Han, Kangkang; Wei, Gao; Lei, Siyuan; Qiu, Changlong; Qiu, Tiancheng
Abstract: In this article, a broadband dual circularly polarized (CP) antenna with simple structure and high gain is designed. A metal ridge septum with the shape of the cascade of a rectangle and a triangle is embedded into the square waveguide to excite CP wave, which is presented through analysis and simulation. By feeding the antenna at the two positions with respect to the symmetrical position of the septum, it can form the right‐handed circularly polarized (RHCP) and left‐handed circularly polarized (LHCP) wave, respectively. To verify the design, a prototype of the antenna is fabricated and measured. The measured and simulated results coincide with each other. According to the simulation and measurement, the designed antenna can work well within a relative bandwidth of 64% from 8.5 to 16.5 GHz. The proposed dual CP antenna has the simple configuration and good performance, and it can be a good candidate antenna for the broadband communication system.